Developing and Validating Electronic Medical Record Based Case Definitions for Liver Diseases and Comorbidities. (2017) - Xu, Yuan; Li, Ning; Lu, Mingshan; Myers, Robert; Dixon, Elijah; Walker, Robin; Quan, Hude
No abstract available